Borrelia burgdorferi and tick proteins supporting pathogen persistence in the vector. (January 2013) - Kung, Faith; Anguita, Juan; Pal, Utpal
Borrelia burgdorferi, a pathogen transmitted by Ixodes ticks, is responsible for a prevalent illness known as Lyme disease, and a vaccine for human use is unavailable. Recently, genome sequences of several B. burgdorferi strains and Ixodes scapularis ticks have been determined. In addition, remarkable progress has been made in developing molecular genetic tools to study the pathogen and vector, including their intricate relationship. These developments are helping unravel the mechanisms by which Lyme disease pathogens survive in a complex enzootic infection cycle. Notable discoveries have already contributed to understanding the spirochete gene regulation accounting for the temporal and spatial expression of B. burgdorferi genes during distinct phases of the lifecycle. A number of pathogen and vector gene products have also been identified that contribute to microbial virulence and/or persistence. These research directions will enrich our knowledge of vector-borne infections and contribute towards the development of preventative strategies against Lyme disease.